NORMATIVE STUDY OF COMPENSATION FOR FIXED-TIME WORK AGREEMENTS (PKWT) BASED ON THE JOB CREATION LAW - Solahudin, Ade (Ann Publisher, 2025)
Abstract Background. The dynamics of labor regulation reform need to be analyzed for the benefit of the community in general and workers/laborers in particular. Aims. Since the implementation of Law No. 11 of 2020 concerning Job Creation and Government Regulation No. 35 of 2021 concerning Fixed-Time Work Agreements, Outsourcing, Working Time, Employment Relations and Rest Time, and Termination of Employment, there have been deletions, updates, and additions to articles related to labor law. Methods. In this study, normative juridical research is applied, which emphasizes the analysis of legal products such as laws and regulations but still pays attention to the reality in society related to the problem to be discussed. Result. This study reviews regulatory updates, including an analysis of Fixed-Time Work Agreements (PKWT) rules in the Job Creation Law. The provisions of PKWT have changed, namely, workers/laborers whose contract period has been completed are entitled to compensation money or severance pay. Conclusion. This is a new thing, so this study aims to analyze in a normative juridical manner the provisions for providing compensation or severance pay, starting from the distribution of the amount to the sanctions for the company if it violates it. Implementation. Many entrepreneurs still do not implement the law. Sanctions must be applied, namely, administrative sanctions such as written reprimands, restrictions on business activities, temporary suspension of part or all of production equipment, and freezing of business activities.